Suppression of hematopoietic cell kinase ameliorates the bone destruction associated with inflammation. Issue 1 (2nd January 2020) - Kim, Yusoon; Hayashi, Mikihito; Ono, Takehito; Yoda, Tetsuya; Takayanagi, Hiroshi; Nakashima, Tomoki
Abstract: Objectives: To investigate the role of non-receptor tyrosine kinases (NRTKs) in inflammation-induced osteoclastogenesis. Methods: Microarray analyses of global mRNA expression during receptor activator of NF-κB ligand (RANKL) and RANKL plus tumor necrosis factor (TNF)-α-induced osteoclast differentiation were performed. The inhibitory effect on TNF-α-induced osteoclast differentiation of A-419259, a potent inhibitor of hematopoietic cell kinase (Hck), was examined. The in vivo therapeutic effect of A-419259 treatment on lipopolysaccharide (LPS)-induced inflammatory bone destruction was evaluated. Results: We confirmed that Hck expression was selectively increased among the NRTKs during the osteoclast differentiation induced by RANKL and TNF-α, but not by RANKL alone. RANKL and TNF-α-induced osteoclast differentiation and they were dose-dependently inhibited by A-419259 treatment through inhibition of the expression of key regulators of osteoclastogenesis, including Prdm1 and Nfatc1 . Notably, LPS-induced inflammatory bone loss in murine calvarial bones was ameliorated by the administration of A-419259. Conclusions: Our results demonstrate that the administration of A-419259 is effective for the inhibition of osteoclast differentiation induced by TNF-α in the presence of RANKL. Therefore, an inhibitor of Hck may be useful as a potent anti-osteoclastogenic agent for the treatment of inflammatory bone destruction.